2021
DOI: 10.1371/journal.pntd.0009129
|View full text |Cite
|
Sign up to set email alerts
|

Costs and outcomes of active and passive case detection for visceral leishmaniasis (Kala-Azar) to inform elimination strategies in Bihar, India

Abstract: Background Effective case identification strategies are fundamental to capturing the remaining visceral leishmaniasis (VL) cases in India. To inform government strategies to reach and sustain elimination benchmarks, this study presents costs of active- and passive- case detection (ACD and PCD) strategies used in India’s most VL-endemic state, Bihar, with a focus on programme outcomes stratified by district-level incidence. Methods Expenditure analysis was complemented by onsite micro-costing to compare the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Reactive policies, which would increase detection and treatment, would strengthen the use of passive surveillance but may be challenging if passive surveillance systems are not able to detect ongoing transmission at low levels [ 13 ]. For example, for visceral leishmaniasis prevalence has been shown to have an effect on the effectiveness of passive and active case detection [ 14 ]. These types of dynamics could be due to both program effects (how good healthcare is at diagnosing when a case turns up) and population effects (how good people are at going to healthcare depending on awareness and perception of risk).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive policies, which would increase detection and treatment, would strengthen the use of passive surveillance but may be challenging if passive surveillance systems are not able to detect ongoing transmission at low levels [ 13 ]. For example, for visceral leishmaniasis prevalence has been shown to have an effect on the effectiveness of passive and active case detection [ 14 ]. These types of dynamics could be due to both program effects (how good healthcare is at diagnosing when a case turns up) and population effects (how good people are at going to healthcare depending on awareness and perception of risk).…”
Section: Discussionmentioning
confidence: 99%
“…In the same way in high endemic districts, more cases were identified by passive case‐detection (PCD), despite routine surveillance does not usually permit accurate assessments of any changes in the incidence of leishmaniasis (Ready, 2014). While in meso‐ and low‐endemic districts, more cases were identified by ACD; however, the cost of extending the ACD was expensive (Dial et al., 2021). These ACD strategies not only reduce the time to diagnosis (Rubiano et al., 2021) and thus the risk of transmission (Dubey et al., 2021) but also contribute to regional reduction of leishmaniasis (Das et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, active case detection in VL cases significantly reduced the time from the onset of fever to diagnosis [132]. Studies revealed that the cost of early detection of further VL and CL cases is lower than outweighs the long-term costs for achieving VL and CL elimination benchmarks [133,134]. Also, active case detection is cost-effective in regions where the incidence rate is high [133].…”
Section: Health Personnelmentioning
confidence: 99%
“…Studies revealed that the cost of early detection of further VL and CL cases is lower than outweighs the long-term costs for achieving VL and CL elimination benchmarks [133,134]. Also, active case detection is cost-effective in regions where the incidence rate is high [133]. Furthermore, active case detection and early treatment of ACL cases could be effective approaches to controlling the disease, especially in times of epidemics such as in the earthquake in Bam, Iran [135].…”
Section: Health Personnelmentioning
confidence: 99%